GAMBARAN PENDERITA DIARE PADA BALITA DI UPTD PUSKESMAS II DINAS KESEHATAN KECAMATAN DENPASAR BARAT PERIODE JUNI-NOVEMBER TAHUN 2019 - Fakhrurrozi, M.; Subrata, I Made (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021DO - 10.24843/ACH.2021.v08.i03.p02, 2022)
ABSTRACT In Denpasar City, in 2019 it was found and served as many as 4923 toddlers with diarrhea or 30.8% of the estimated number of cases. This study aims to find out the description of diarrhea sufferers in toddlers at the UPTD Puskesmas II, West Denpasar District Health Office for the period of June-November 2019. This research is a quantitative research, with a descriptive research design and using a cross sectional research design. The total sample is 79 toddlers. The sampling technique used was total sampling. Data sourced from secondary data from UPTD Puskesmas II, West Denpasar District Health Office. Data analysis used univariate analysis. The results and conclusions of the study show that at the UPTD Puskesmas II, West Denpasar District Health Office, for the June-November period 2019. The most diarrhea sufferers are male toddlers, as much as 60.76%. Diarrhea sufferers in toddlers mostly occurred in the age category 12-36 months as much as 54.43%. The most diarrhea sufferers in toddlers from Padangsambian Kelod Village were 32.91%. The majority of patients with diarrhea without dehydration were 75.95% under five, there were also 24.05 patients with mild/moderate dehydration. There are 26.58% of toddlers with diarrhea get Ringer's lactate fluid. There are 12.66% of toddlers with diarrhea who get antibiotics. It is recommended that the Puskesmas through the posyandu carry out more intensive socialization programs related to prevention and treatment measures for parents who have toddlers, especially boys and toddlers aged 12-36 months. Key words: Diarrhea, Toddlers, Dehydration, Public Health Center II, West Denpasar